EFFECT ON PROMOTION AND SERVICE QUALITY ON CUSTOMER SATISFACTION IN PADANG OPTICS - Alvia Wesnita; Mega Elfia; Alwa Pascaselnofra Amril (Jurnal Mata Optik, 2021)
This scientific paper aims to determine the relationship between promotion and service quality on customer satisfaction in Optik Padang. This type of research is descriptive quantitative. The study population was 101 Optics Minang Padang customers, the sampling was randomly proportional to the number of 50 customers. The results of the univariate multiple regression analysis Promotion in Optik Minang Padang, the R value is 0.142. The value of R Square (R2) is 0.02 which means (2%) the value of promotion contributes to customer satisfaction with a significance of 0.021 where the p value is <0.05. Meanwhile, Padang Minang Optical Service Quality Value R Square (R2) of 0.243 means (24.3%) the value of service quality contributes to the significance of customer satisfaction by 0.000, which p value <0.05. Furthermore, the results of the multiple regression R test of 0.493 which shows a significant simple regression coefficient. quality of service to customer satisfaction. The value of R Square (R2) is 0.256 which means (25.6%) Significance of 0.001 where the p value is <0.0. Based on the results of this study, it is suggested to the Optic Owner to increase promotion and service quality and that RO can work professionally.